Pedagogy of Liberation: A Case of Nepal - Baral, Roshan Raj (New Angle: Nepal Journal of Social Science and Public Policy, 2011)
This paper looks into the experiment of New Democratic Education (NDE) as an alternative to the mainstream education in Nepal. It was carried out in Nepal by CPN (Maoist) during the period of People’s War from 1996 to 2006. Along with the emergence of new people’s government in western hilly districts of Nepal by 2003, the concrete foundation was laid to establish ‘new democratic schools’ with their own curriculum. Such a radical pedagogical intervention was in fact an attempt to oppose the present education system which is elitist in its model. The paper endeavours to examine the development and implementation of the NDE project in western Nepal. With the exploration of its curriculum including objectives, textbooks, instruction methods and evaluation system, this paper tries to depict the alternative discourse of school education backed by this experiment in Nepal as well as the counter-arguments. The method of the study constitutes review of the relevant documents and interviews.